2015
DOI: 10.5152/dir.2014.14187
|View full text |Cite
|
Sign up to set email alerts
|

Variations in apparent diffusion coefficient values following chemotherapy in pediatric neuroblastoma

Abstract: ORIGINAL ARTICLE PURPOSEIn children the assessment of solid tumors' response to chemotherapy is based primarily on size reduction, which can be unreliable and a late marker, in the presence of necrosis. We aimed to establish whether apparent diffusion coefficient (ADC) values of childhood neuroblastomas show proportional changes in relation to chemotherapy response. METHODSWe evaluated 15 pediatric patients with abdominopelvic neuroblastomas, who had undergone MRI before and after chemotherapy. Two radiologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Preliminary results suggest that, based on apparent diffusion coefficient (ADC) values, DWI can indeed distinguish between NB, GNB and GN with some confidence [10,11]. Recent reports confirm these findings [12] and propose diagnostic value for detecting metastases [13] and for monitoring therapy response [14].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Preliminary results suggest that, based on apparent diffusion coefficient (ADC) values, DWI can indeed distinguish between NB, GNB and GN with some confidence [10,11]. Recent reports confirm these findings [12] and propose diagnostic value for detecting metastases [13] and for monitoring therapy response [14].…”
Section: Introductionsupporting
confidence: 54%
“…Demir et al [14] recorded significantly higher mean, maximum and minimum values for tumor ADC in 15 children undergoing DWI at 1.5 T (Magnetom Symphony and Magnetom Avanto) of 1.05 with therapy, compared to 0.74 on pre-therapy DWI, using a small ROI approach. These data are virtually identical to the data obtained with the small ROI evaluation in our study (▶ Table 1), further supporting our notion of good reproducibility of ADC quantification when using similar equipment and scanning parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, DWIBS has been confirmed, based on ADC values of the original lesions, to discriminate between benign and malignant tumors including neuroblastic tumors [ 15 19 ] and also to efficiently judge response to chemotherapy in pediatric neuroblastoma [ 20 ]. In adult patients, however, there have been reports indicating that signal intensity of the lesion-to spinal cord ratio (LSR) measured on high b-value DWIBS is more useful than ADC for differentiating between benign and malignant lung nodules [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of pediatric oncology, it has recently been demonstrated that, based on apparent diffusion coefficient (ADC) values, DWIBS can discriminate between benign and malignant abdominal mass lesions [ 15 ], between neuroblastoma and ganglioneuroma/ganglioneuroblastoma [ 16 18 ], and between neuroblastoma and Wilms tumor [ 19 ]. Change in ADC values is useful for efficiently judging response to chemotherapy in pediatric neuroblastoma [ 20 ]. There has also been a case report which proposes diagnostic value of DWIBS for detecting metastases of pediatric neuroblastoma [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, both CT and MRI have low positive predictive value for LNI, but the inclusion of additional pulse sequences, such as diffusion weighted imaging, as part of a multiparametric MRI may improve positive lymph node detection ( 4 ). Use of ADC mapping values calculated from diffusion-weighted imaging with background body signal suppression (DWIBS) has been shown to differentiate NB from other abdominal lesions, both benign and malignant, and gauge response to chemotherapy ( 38 , 39 ).…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%